2019
DOI: 10.2147/copd.s213947
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chronic Obstructive Pulmonary Disease In Aboriginal Patients Of The Northern Territory Of Australia: A Landscape Perspective</p>

Abstract: Background: The Aboriginal population of Australia has a higher burden of chronic health conditions than non-Aboriginal Australians. However, there is a paucity of data on clinical and demographic characteristics of chronic obstructive pulmonary disease (COPD) in this population. Method: In this retrospective study we evaluated the clinical, demographic and environmental influences in adult Aboriginal patients with COPD living in the regional and remote communities of the Northern Territory of Australia. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 35 publications
0
82
1
Order By: Relevance
“…However, measurement of DLCO and TLC values via body plethysmography would face significant challenges in this population, where 81% of Indigenous people reside in remote or very remote communities, many of which may be accessed only seasonally by light aircraft ( S1 and S2 Figs) within a vast geographic area of 245,000 km 2 (94,595.0 sq mi) and a population density of 0.16 people per kilometre, making such a study virtually infeasible [ 29 , 30 ]. Therefore, the use of a portable DLCO ndd device is the most reasonable method to assess LFP’s for Indigenous subjects during respiratory specialist outreach visits to remote Indigenous communities ( S3 Fig )—a unique model adopted for respiratory care in the TEHS region of NT of Australia [ 2 , 3 , 11 ]. The authors are also very aware and acknowledge that the sample size may be less than ideal for this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, measurement of DLCO and TLC values via body plethysmography would face significant challenges in this population, where 81% of Indigenous people reside in remote or very remote communities, many of which may be accessed only seasonally by light aircraft ( S1 and S2 Figs) within a vast geographic area of 245,000 km 2 (94,595.0 sq mi) and a population density of 0.16 people per kilometre, making such a study virtually infeasible [ 29 , 30 ]. Therefore, the use of a portable DLCO ndd device is the most reasonable method to assess LFP’s for Indigenous subjects during respiratory specialist outreach visits to remote Indigenous communities ( S3 Fig )—a unique model adopted for respiratory care in the TEHS region of NT of Australia [ 2 , 3 , 11 ]. The authors are also very aware and acknowledge that the sample size may be less than ideal for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic health conditions are noted to be highly prevalent in Indigenous populations, including Australian Aboriginal people. [40][41][42][43][44][45][46] Under diagnosis or untreated OSA in this population may give rise to adverse health outcome. 47 Ethnic and gender differences need to be considered in the clinical assessment of patients with OSA, which may itself represent a different phenotype.…”
Section: Dovepressmentioning
confidence: 99%
“…Indigenous people around the world experience a higher burden of chronic health conditions, including advanced respiratory conditions. [44][45][46] Despite evidence in the literature to suggest chronic respiratory conditions along with poor LFPs are highly prevalent among Indigenous population, including in the adult Indigenous Australians, 1,4,[7][8][9][10][11][12][13][14][15][16] there is no published data examining the effects of airway directed inhaled pharmacotherapy on LFPs trajectory in this population. Hence, we believe our current study is of significant value in addressing this gap in our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Chronic airway diseases, such as COPD and bronchiectasis are noted to be highly prevalent in the NT Indigenous population. [7][8][9][10][11] Moreover, recently published data has shown that co-occurrence of COPD and bronchiectasis along with poor lung function parameters (LFPs) are highly prevalent among Indigenous people living in the Top end health service (TEHS) region of the NT of Australia. [12][13][14][15][16] LFTs 17 play an integral role in the diagnosis, management and monitoring of several respiratory conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation